Integration of human factors, cognitive ergonomics, and artificial intelligence in the human-machine interface for additive manufacturing. (22nd November 2022) - Doran, Eric; Bommer, Sharon; Badiru, Adedeji
As additive manufacturing transitions from manufacturing prototypes to rapid manufacturing, more human factors considerations must be assessed and integrated for improved work design. This review paper provides an overview of human-machine integration for human factors, cognitive ergonomics, and artificial intelligence to improve the performance output of the additive manufacturing process. In addition, case studies are shared to provide integration concepts for artificially intelligent systems. It is anticipated that the contents of this review paper will pave the path for further research into the integration of human factors and cognitive ergonomics for artificial intelligence in additive manufacturing.